The Effect of Word Square Model on Improving Vocabulary Mastery of Class VIII Students - Sumandari, Sri; Mahyudin Ritonga (Journal of Practice Learning and Educational Development, 2026)
This research is based on the researcher’s findings regarding the low ability of students in mastering vocabulary. Vocabulary is the most important foundational element in learning the Arabic language. This study aims to analyze the effect of the Word Square model on the vocabulary Mastery of Class VIII Students at MTS Nurul Haq Semurup. The research is designed as a quantitative study using a quasi-experimental method, which is conducted by comparing the experimental group before receiving the treatment and after receiving the treatment. The instrument used to obtain the data consisted of a pre-test and a post-test. The population in this study was all students of class VIIIB at MTS Nurul Haq Semurup in the 2024/2025 academic year, with a sample of 24 students. Based on the data analysis, the results of the t-test show that the significance value (Sig. 2-tailed) is 0.000, which is less than 0.05. Thus, it can be concluded that H0 is rejected and Ha is accepted, indicating that there is a significant effect of using the Word Square model in improving students’ vocabulary mastery.